Non-thermal processes in the bow shocks of hyper-velocity stars - Martínez, Javier Rodrigo (2021)
Runaway stars move at supersonic speed with respect to their surrounding medium. Such stars generate bow shocks in the interstellar gas as they propagate. These bow shocks are usually studied by means of the infrared radiation and the optical emission lines produced by the forward shock. However, bow shocks can also accelerate particles up to relativistic energies, which in turn produce broadband non-thermal emission. This radiation has been investigated in the reverse shocks of runaway stars with velocities of < 100 kms-1. In this work, we expand the research to the case of hyper-velocity stars with speeds reaching thousands of km s-1. We analyze their potential as particle accelerators and non-thermal radiation sources. In particular, we show that non-thermal processes are relevant in both the reverse and forward shocks. We estimate the broadband spectra and assess their detectability as a function of different parameters such as their spectral type, spatial velocity, and the medium density.